Tuning Zn2+ coordination environment to suppress dendrite formation for high-performance Zn-ion batteries. (February 2021) - Qin, Runzhi; Wang, Yuetao; Zhang, Mingzheng; Wang, Yan; Ding, Shouxiang; Song, Aoye; Yi, Haocong; Yang, Luyi; Song, Yongli; Cui, Yanhui; Liu, Jian; Wang, Ziqi; et al.
Abstract: The short-circuit issue induced by Zn dendrite growth restricts the commercialization of rechargeable aqueous Zn-ion batteries (ZIBs). Herein, ethylene glycol (EG), a representative of dihydric alcohols, is applied in the aqueous electrolyte to inhibit the detrimental dendrite growth on Zn anode. Our work demonstrates a uniform Zn plating/stripping in H2 O/EG hybrid electrolyte with cycling lifespan of up to 2668 h at 0.5 mA cm −2, which is made possible by the substitution of EG for H2 O in the solvation sheath of Zn 2+ ions. Such a change in the coordination environment of Zn 2+ gives rise to decreased diffusivity of the ions and increased over-potential for nucleation, further resulting in even deposition morphology rather than large-scale dendrites. Side reactions are also circumvented by the formation of hydrogen bonds. All these aspects work in synergy to promote the cyclability of the assembled full battery. The low-cost aqueous electrolyte identified in this work opens up new opportunities for manipulating the coordination environments of Zn 2+ ions and optimizing the Zn deposition morphology during the design of high-performance ZIBs. Graphical Abstract: ga1 Highlights: Cycling performance of Zn electrodes is greatly enhanced via adding ethylene glycol (EG). Tuning Zn 2+ coordination by EG contributes to uniform Zn deposition, as well as higher CE. Adding EG benefits for cycling performance and low-temperature performance of Zn/ZnVO full batteries.